Multicultural Citizenship and the Status of ‘Others’ in the Post 1991 Ethiopia: A Study on Membership and Self-Governing Status of Amhara People in Benishangul-Gumuz Regional State - Ketemaw Tiruneh Muluye (RUDN Journal of Public Administration, 2019)
Following the regime change in 1991, the Ethiopian government sought to institutionalize inclusive multicultural citizenship in the country. Membership status and selfgoverning rights are crucial entitlements in the multiculturalists’ notion of citizenship. Though citizenship is considered to be part of domestic affairs of a state, it is also influenced by the policies of sub-state political units. Hence, this paper examines the membership and self-governing status of Amhara and analyzes how the citizenship status is affected at sub-state units, with a focus on Benishangul Gumuz Regional State. Concurrent embedded mixed approach was employed and data were collected through interviews and document analysis. Interview data were obtained from 29 respondents, chosen by means of an intensity sampling method. Quantitative data were also acquired from Ethiopian Central Statistical Agency. The data were analyzed qualitatively with some quantitative backup. Though Amhara People of BGRS have the legal status of Ethiopian citizenship, BGRS has failed to fully integrate these people to the mainstream political community. Particularly, the exclusionary politics of recognition (as only selected nationalities receive the so-called ownership of the region ) and the prohibition of Amhara from exercising selfgovernment rights (this right is exclusively given to the ‘owner’ nationalities by the regional constitution) demonstrate the hierarchy of citizenship, where Amhara people are treated as secondclass citizens in BGRS, which is contradictory to the notion of multicultural citizenship.